2010
DOI: 10.1080/10826060903558588
|View full text |Cite
|
Sign up to set email alerts
|

PURIFICATION AND CHARACTERIZATION OF CURCIN, A TOXIC LECTIN FROM THE SEED OFJATROPHA CURCAS

Abstract: The seed of the plant Jatropha curcas contains a toxic protein, designated as curcin, which was purified to apparent homogeneity by the combined use of chromatography on Sephdex G-100. The molecular weight of 28.2 kDa and the pI of 8.54 were determined. The protein was found to be a glycoprotein; the total neutral-surge content was 4.91%. It strongly inhibits the protein synthesis of rabbit reticulocyte lysate, with an IC(50) of 0.42 nM. It was determined by Edman that the sequence of the N-terminal thirty-two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 22 publications
1
21
0
5
Order By: Relevance
“…The glycosylation, molecular weight, pI, and sugar content data are in accordance with the values reported by Stirpe 29) for RIPs and Lin et al 30) for curcin.…”
Section: Resultssupporting
confidence: 76%
“…The glycosylation, molecular weight, pI, and sugar content data are in accordance with the values reported by Stirpe 29) for RIPs and Lin et al 30) for curcin.…”
Section: Resultssupporting
confidence: 76%
“…3B). Purified hemagglutinin from J. curcas seeds had a pI value of 5.75 (Cano-Asseleih et al, 1989), while in curcin, the pI value was 8.54 (Juan Lin et al, 2010).…”
Section: Ief Of Protein Fractions From J Curcas Seedsmentioning
confidence: 99%
“…The albumin 2S (~ 12 kDa) was identified as the first known allergen from J. curcas (Menezes et al, 2009). J. curcas also contains a toxic protein, named curcin, with a molecular weight of ~ 28.2 kDa (Juan Lin et al, 2010) similar to that found in albumin and prolamin fractions.…”
Section: Electrophoresis Of Protein Fractions From J Curcas Defattedmentioning
confidence: 99%
“…Bungkil sisa pengepresan jarak pagar juga diketahui mengandung curcin yang bersifat sangat toksik. Curcin dapat menyebabkan iritasi pada mata, dan keracunan pada hewan peliharaan (Stirpe et al 1976;Devappa et al 2010;Lin et al 2010).…”
Section: Hasil Dan Pembahasanunclassified